IL6 trans-signalling is associated with a higher risk of cardiovascular events in individuals with diabetes. (14th October 2021) - Ziegler, L; Gigante, B
Abstract: Background: Pro-inflammatory interleukin 6 (IL6) trans-signalling is associated with an increased risk of future cardiovascular events (CVE). Diabetes mellitus is a well-known risk factor for CVE but its relation to IL6 trans-signalling is not investigated. Purpose: We aimed at analysing if the CVE risk associated with IL6 trans-signalling differed between individuals with/without diabetes. Method: In a prospective cohort of 60-year-old men and women from our city (n=4232), 629 CVE (myocardial infarction, hospitalised angina pectoris and ischemic stroke) occurred during a 20-year follow-up. The risk of CVE associated with IL6 trans-signalling was assessed using the binary/ternary complex ratio (B/T ratio), a novel marker of IL6 trans-signalling derived from the serum molar concentrations of IL6 and the soluble IL6 receptors (sIL6R; sgp130). As a B/T ratio > median, mirroring active IL6 trans-signalling with a relative excess of the active binary IL6 complex in relation to the inactive ternary complex, previously was demonstrated to be associated with an increased CVE risk in this cohort we chose the same cut-off. The CVE risk was assessed by Cox proportional hazards models and described as hazard ratios (HR) with 95% confidence intervals (CI) in individuals with/without diabetes mellitus type 1 or 2 (n=114) defined as either self-reported, or fasting glucose >7.0 mmol/L in the baseline blood test. In the adjusted model, risk estimates were adjusted for the common cardiovascular risk factors. The additive interaction between IL6 trans-signalling and diabetes on the CVE risk was analysed using Cox regression and presented as Synergy index (S) with 95% CI where S > or <1 indicate presence of an interaction. Result: There was a higher CVE risk associated with IL6 trans-signalling assessed by B/T ratio > median in individuals with diabetes (adjusted HR 3.42; 95% CI 1.60–7.29) compared to participants without (adjusted HR 1.36; 95% CI 1.15–1.60) and the interaction analysis suggested a presence of additive interaction between IL6 trans-signalling and diabetes on the CVE risk (adjusted S=5.23; 95% CI 0.93–29.26) as seen in Figure 1. Conclusion: Individuals with diabetes mellitus have an increased risk of CVE associated with IL6 trans-signalling possibly in part due to an additive interaction between the two. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The Stockholm County Council ALF projectStrategic research in Epidemiology at Karolinska Institutet